Effect of seasonal dietary changes on hematology and iron biochemistry of crossbred cattle in Punjab - BHARDWAJ, R K; RANDHAWA, C S; RANDHAWA, S S; DHAIWAL, P S (The Indian Journal of Animal Sciences, 2011)
Cross~red cows (35) at least 10 each, frail} 3 luanagement systen1s with low medium and good plane of nutrition were studied. The blood salnples were collected from each group on 6 occasions July-.Aug CSt), Sep-Oct (S2), Nov-Dec (S3), Jan-Feb (S4), Mar-Apr (Ss) and May-June (S6) to estimate red cell parameters and iron metabolis111 analytes to represent 6-periods. Mean values of Hb and PCV were low during July-Aug and Sep-Oct periods and increased significantly during Jan-Feb and Mar-Apr periods. Prevalence rate of seasonal anaenlia was 40% during July-Aug, 34.2% during Sep-Oct and 8.820/0 during Nov-Dec periods. Plasma iron concentrations were highest during Sep-Oct and Nov-Dec and lowest during May-June in all groups. Conversely values of total iron binding capacity (TIBC) were highest during 86 and lowest during S2 and S3 periods. Per cent transferrin saturation (PTS) followed the same trend as observed in plasma iron concentration.Â